2016
DOI: 10.1016/j.optmat.2016.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Optical, scintillation and dosimeter properties of MgO translucent ceramic doped with Cr3+

Abstract: We have investigated the photoluminescence (PL), scintillation and thermally-stimulated luminescence (TSL) dosimeter properties of MgO translucent ceramic doped with Cr 3+ ion (0.001, 0.01 and 0.1 %). The ceramic samples were synthesized by a Spark Plasma Sintering (SPS) technique. The broad and sharp emission peaks appeared around 600-850 nm in all the samples. The PL decay time constants of all the samples were a few ms which were on the typical order of Cr 3+ doped phosphors. As with the PL, the peak result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…The E g of MNPs was remarkably lower than the energy band gap from the standard value of Eg in the bulk state (7.8 eV) due to red-shifted from the standard. This was related to the [19,20]. Also, these results were in good match with other previous works which used pure precursor for the synthesis of MgO nanostructures [1,5,[21][22][23][24].…”
Section: Optical Propertiessupporting
confidence: 90%
“…The E g of MNPs was remarkably lower than the energy band gap from the standard value of Eg in the bulk state (7.8 eV) due to red-shifted from the standard. This was related to the [19,20]. Also, these results were in good match with other previous works which used pure precursor for the synthesis of MgO nanostructures [1,5,[21][22][23][24].…”
Section: Optical Propertiessupporting
confidence: 90%
“…The spectrum of 3d-3d and 4d-4d (d-d) transitions has a broad luminescence feature, and the decay time is typically on the ms order. Among the transitional metal elements, Mn 2+ 65 and Cr 3+ 66 are sometimes selected for scintillation detectors due to a good spectral matching with Si-PD.…”
Section: Recent Randd Progress Of Scintillatorsmentioning
confidence: 99%
“…We are primarily concerned with our wavelengths of interest (800 nm and 400 nm). Cr: MgO has shown that transmission of optical light decreases overall with increasing doping concentration [21], relevant for both our wavelengths of interest.…”
Section: Doping Impact On the Yield Of Shgmentioning
confidence: 93%